ZD7288 ameliorates long-term cerebral ischemia reperfusion-induced deterioration of spatial memory by regulating the expressions of NMDA receptor subunits in rats - Zhi He; Xiao-Jiao Chu; Xiao-Li Zeng; Xiao-Xue Zhang; Jing Chen; Ke Wang; Yue Chen; Zi-Cheng Li; Bo Zhao (Scientific Reports)
Abstract To study the effect of inhibition of hyperpolarization-activated cyclic nucleotide-gated cation channel (HCN) on spatial memory with cerebral ischemia-reperfusion (IR) in rats, the middle cerebral artery occlusion was performed to induce the IR injury. ZD7288 (5 µg/µl) and MK-801 (100 µg/µl) were administrated by lateral ventricular injection. Except for the sham group, all other groups were subjected to ischemia for 2 h followed by reperfusion for 4 weeks. The neurological impairment was evaluated using the neurological deficit score, and the Morris water maze detected changes in spatial memory. The cerebral infarction volume was determined by TTC staining, and the morphology and number of hippocampal neurons on the ischemic side were observed through HE staining. Immunoblotting and qPCR were used to detect the expressions of HCN1, HCN2, and N-methyl-D-aspartic acid receptor (NMDAR) subunits in the hippocampus. The expression changes of NMDAR subunits were applied by immunohistochemistry in different hippocampus regions. Our study found that ZD7288 could improve the spatial memory deficits induced by IR and exert neuroprotective effects. The possible mechanism is related to the fact that ZD7288 regulates the expression of various subunits of NMDAR by inhibiting HCN, including its effect on their phosphorylation states.